Kepastian Hukum atas Harta dalam Perkawinan Menurut Hukum Perdata Terkait Akta Perjanjian Kawin Pisah Harta yang Lalai Didaftarkan - Raharja, Randy; Marniati, Felicitas Sri; Yani, Ahmad (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
Marriage relations between men (husbands) or women (wives) will cause marital property, joint property sometimes causes problems when divorce occurs. The subject of this research is how the implementation of the marriage agreement deed related to the separation of property according to civil law made by the negligent parties is registered and how the legal certainty of joint property according to the marriage law related to the negligent marriage agreement deed is registered and how the legal certainty is. The method used in this study is a type of normative juridical research, namely literature law research with sources of primary, secondary, and tertiary legal materials. The research approach used is the Legislative Approach, Conceptual Approach, Analytical Approach, Case Approach, and legal material collection techniques are carried out by identifying and inventorying positive legal rules, book literature, journals, and other sources of legal materials. Legal material analysis techniques, grammatical interpretation, systematic interpretation, and legal construction methods are carried out. The results of the study show that the legal certainty of joint property according to civil law related to the deed of negligent marriage agreement is registered after the existence of PMK Number 69/PUU-XIII/2015 through the marriage agreement of Indonesian Citizens (WNI) and Foreign Citizens (WNA) based on the Court Decision, a marriage agreement for the separation of property can be carried out after the marriage, to avoid before problems arise and/or contrary to the Law which applies in Indonesia over the right to own property status during marriage